Analisis Persepsi Karyawan Terhadap Praktek-Praktek Organisasional Terkait Layanan dan Komitmen Organisasional Serta Pengaruhnya Terhadap Iklim Layanan Pelanggan - Siti Nursyamsiah; Prapti Antarwiyati (Jurnal Siasat Bisnis, 2008)
This study examines the relationships between certain organizational variables and employees`perceptions of the customer service climate in their organization. The sample of study is the entire administration employee of Higher Education in Yogyakarta. The research has discovered some evidence that reward is not affecting employee`s perception toward Customer service Climate. However, it is affecting the Organizational Commitment. If the employee`s demand is accepted well by the management, then they will do the some thing to the customer. Hence, it will influence the organizational commitment. Providing sufficient Work Environment and Training able to show the institution efforts on employee`s wealth. Other evidences show that, partially, Work Design, Work Environment and Training, mediated by Organization Commitment. This evidence shows the good working design, adequate working environment and training to employee will influence the increase of organizational commitment. Thus, it will influence the employee`s perceptions towards Customer Service Climate.Keywords: customer service climate, organizational commitment, employee perceptions